Cross-border mergers and acquisitions: Mature markets vs. emerging markets—with special reference to the USA and India - Geeta Rani Duppati; Narendar V. Rao (Cogent Business & Management, 2015)
Due to the differences in the merger waves across markets, the market for cross-border mergers and acquisitions by Indian companies differs in context and situations from those of the mature markets. Post-acquisition performance is critical to the success of companies involved in overseas investments. This paper uses event study methodology to analyse the long-term performance of Indian-acquiring companies by undertaking 30 outward foreign direct investment (OFDI)-related deals, during 2000–2008 period. Further, it compares the empirical findings from India with the prior findings from the USA. It is evident from the empirical results that the stock markets reacted positively in the short run following the announcements of the OFDI-related mergers and acquisitions by Indian companies. The empirical findings also showed positive results in the post-acquisition period following the overseas deals.
Keywords: 650